- Policies to counteract the anticipated effects of the oil price crash - - The case of Algeria - Toumi, Rihabelislam; Chibout, Slimane (Journal of Excellence for Economics and Management Research, 2020)
Algeria like various developing countries, has been working since its independence to take measures and measures to regulate its foreign trade sector in a way that serves the set of economic goals set by the state in every period. The country as a whole and its various economic, social and environmental aspects, and trade policy is considered the most important link between countries in the field of commercial dealings and exchanges. Especially on countries that depend in particular on the hydrocarbon sector, and oil has now become the direct role in managing the wheel of economic growth and in moving the realities of global conflicts due to the world’s growing need for energy imposed by economic and social development and demographic growth, and trade policy has goals like other policies that aspire Through achieving the goal of external balance, which is considered one of the main goals of trade policy, so that it does not fall into crises that might upset the economic system.